1994
DOI: 10.1128/aem.60.6.1754-1761.1994
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Symbiotic Characteristics of a Bradyrhizobium Population Recovered from a Pasture Soil

Abstract: We examined the genetic structure and symbiotic characteristics of Bradyrhizobium isolates recovered from four legume species (Lupinus albus [white lupine], Lupinus angustifolius [blue lupine], Ornithopus compressus [yellow serradella], and Macroptilium atropurpureum [siratro]) grown in an Oregon soil. We established that multilocus enzyme electrophoresis (MLEE) can provide insights into the genetic relatedness among Bradyrhizobium strains by showing a positive correlation (r2 = .0.90) between the relatedness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 44 publications
1
8
1
2
Order By: Relevance
“…In this study, we report that there is a lower genetic diversity in A. diazotrophicus recovered from different host species collected in widely separated regions of the world in comparison to the majority of other bacterial species studied (6,9,10,13,14,19,29,35,44). The results confirm previous data (8) on genetic diversity among 21 Mexican and 3 Brazilian isolates exclusively recovered from sugarcane plants.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we report that there is a lower genetic diversity in A. diazotrophicus recovered from different host species collected in widely separated regions of the world in comparison to the majority of other bacterial species studied (6,9,10,13,14,19,29,35,44). The results confirm previous data (8) on genetic diversity among 21 Mexican and 3 Brazilian isolates exclusively recovered from sugarcane plants.…”
Section: Discussionsupporting
confidence: 89%
“…Since a low number of isolates recovered from Cameroon grass and sweet potato were analyzed, it was not possible to determine if certain ETs of A. diazotrophicus are predominantly associated with a particular host species, as observed, for instance, with the pathogen of mammals Bordetella bronchiseptica (28) or with the legume-nodulating Bradyrhizobium sp. (6). However, the results clearly demonstrated that ET 1 was extensively distributed among all host species analyzed.…”
Section: Discussionmentioning
confidence: 79%
“…5) was very closely related to an isolate from the IL-2 population that conferred exceptionally high growth on its native hosts (see experiment 2 of Table 3). Surveys of bacteria associated with domesticated legumes typically find very wide heterogeneity in plant growth with different isolates, including some isolates that nodulate plants without providing any benefit at all to their hosts (e.g., Jordan 1974;Fuhrmann 1990;Bottomley et al 1994). The few studies on undomesticated legumes have reported similar patterns (e.g., Batzli et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Bradyrhizobium strains isolated from Lupinus spp. can form an effective (nitrogen fixing) symbiosis with Ornithopus plants, but the latter plant genus has more stringent nodulation requirements (Bottomley et al, 1994;Ballard, 1996;Stepkowski et al, 2005). At present, strains infecting Ornithopus species have been poorly classified taxonomically.…”
Section: Introductionmentioning
confidence: 99%